Sensor Systems and Software 4th International ICST Conference, S-Cube 2013, Lucca, Italy, June 11-12, 2013, Revised Selected Papers - Zuniga, Marco; Dini, Gianluca; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International ICST Conference on Sensor Systems and Software, S-Cube 2013, held in Lucca, Italy, 2013. The 8 revised full papers and 2 invited papers presented cover contributions on different technologies for wireless sensor networks, including security protocols, middleware, analysis tools and frameworks.
Improving Key Negotiation in Transitory Master Key Schemes for Wireless Sensor Networks -- Resilient Double Weighted Trust based (REDWEST) WSN using SAX -- Over potential-based Battery End-of-Life Indication in WSN Nodes -- Definition and Development of a Topology-based Cryptographic Scheme for Wireless Sensor Networks -- Smart Fence: Decentralized Sequential Hypothesis Testing for Perimeter Security -- Underwater Sensor Networks with mobile agents: experience from the field -- IRIS: A Flexible and Extensible Experiment Management and Data Analysis Tool for Wireless Sensor Networks -- Enabling High-Level Application Development in the Internet of Things -- Comparative LCA Evaluations between Conventional Interventions and Building Automation Systems for Energetic Requalification Activities -- RAISE: RAIlway infrastructure health monitoring using Wireless Sensor Networks.
Keywords: Computer communication systems; Special purpose computers; Application software; Computer security; Computer Communication Networks; Special Purpose and Application-Based Systems; Computer Applications; Systems and Data Security